Optimizing VAT threshold: The key to improving VAT performance - Maharani, Arya Putri (WIM Solusi Prima, 2024)
The low tax ratio in Indonesia is an issue often associated with suboptimal tax revenue performance. This study examines the role of the threshold for Value Added Tax (VAT), which is suspected to significantly influence the optimization of VAT revenue, while also exploring the effect of VAT rate and Gross Domestic Product (GDP) per capita. The study analyze data from member countries of the Organization for Economic Co-operation and Development (OECD) in 2022 using multiple linear regression methods. The results show that increases in the VAT threshold and VAT rate positively impact VAT revenue performance, while an increase in per capita GDP has a negative effect. A higher VAT threshold allows the country to focus on larger taxpayers, while the Micro, Small, and Medium Enterprises (MSMEs) benefit from reduced administrative burdens. These findings can serve as a basis for government evaluation in determining the appropriate threshold and VAT rates to enhance tax revenue performance optimally.